Crystallographic Studies on The Stability of Pharmaceutical Compound - Rizwan (International Journal of Crystalline Materials, 2024)
Crystallographic studies provide detailed insights into the molecular structure and intermolecular interactions within a crystal lattice, which are key determinants of a compound's stability. By analyzing crystal structures, researchers can identify potential polymorphs, solvates, and hydrates that may impact the physical and chemical stability of the drug. This knowledge helps in optimizing formulation strategies, predicting shelf life, and ensuring consistent drug performance. Advanced techniques like X-ray diffraction and neutron diffraction are commonly used to obtain high-resolution structural data, facilitating the design of more stable and effective pharmaceutical products. Furthermore, these studies aid in identifying potential polymorphs, solvates, and hydrates that could impact the drug's performance, thereby guiding the development of more stable and effective pharmaceutical products.
Keywords: Crystal structure, crystallography, polymorphism, solid-state stability, structure-property relationship; thermodynamics